November Storm - Oldshue, Robert (Book collections on Project MUSE., 2016)
"In each of the stories in Robert Oldshue's debut collection, the characters want to be decent but find that hard to define. In the first story, an elderly couple is told that delivery of their Thanksgiving dinner has been canceled due to an impending blizzard. Unwilling to have guests but nothing to serve them, they make a run to the grocery, hoping to get there and back before the snow, but crash their car into the last of their neighbors. In "The Receiving Line," a male prostitute tricks a closeted suburban schoolteacher only to learn that the trick is on him. "The Field Of Machpelah" features a twenty-something, premed dropout who is guarding a cemetery when a man asks to see his wife's prepaid plot before the hospital disconnects her life support. In "Home Depot," a family uses their foul-mouthed love to survive the birth of a malformed child. A psychiatrist confronts his fear of the past to help a patient in the present in "Mass Mental." In "The Woman On The Road," a twelve-year-old girl negotiates the competing demands of her faith and her family as she is bat mitzvahed in the feminist ferment of the 1980s. The lessons she learns are the lessons learned by a ten-year-old boy in "Fergus B. Fergus," after which, in "Summer Friend," two women and one man renegotiate their sixty-year intimacy when sadly, but inevitably, one of them gets ill. "The Home Of The Holy Assumption" offers a benediction. A quadriplegic goes missing at a nursing home. Was she assumed? In the process of finding out, all are reminded that caring for others, however imperfectly--even laughably--is the only shot at assumption we have. In upstate New York, a November storm is one that comes early in the season. If it catches people off-guard, it can change them in the ways Oldshue's characters are changed by different but equally surprising storms"--